Students’ and teachers’ perspectives about using students’ laptops in a career-based technical high school in the United Arab Emirates - Rahman, Isam Hasan Ali Abdul (2012)
The main aim of this research was to explore the students’ and teachers’ perspectives about using students’ laptops in a career-based technical high school in the United Arab Emirates during a time interval of two academic years. The high school goals of adopting the project were to enhance the educational experience of students, to foster learning, and to transform learning into an exciting, fun, and fulfilling experience. Questionnaires were circulated to the students and teachers of the high school after two and three academic years of adopting the One-To-One E-Learning project to ensure the project is doing what it was designed to do and to assess the extent to which the students and teachers support its implementation in their school. The research was conducted over two academic years to own rich data that may construct a solid base for a comparison study. The findings were analyzed and a comparison was held to discover the similarities and differences between the perspectives of students and teachers in the two academic years. One major finding was that the feedback of students was positive and they were clear about their perspectives while their teachers in most of the cases were uncertain and neutral. Another finding is that both of them are supporting the implementation of the project in their school with a high percentage even though they have some concerns. Based on the findings and the comparison, the study suggested conducting a critical review for the policy on adopting the One-To-One E-Learning project in the high school under study, concluded the need for deeper research and wider comparisons, and drew recommendations for further study and implications.